Sporadic inclusion body myositis: an unsolved mystery - Machado, P (2009)
Sporadic inclusion body myositis (sIBM) is considered to be the most common acquired muscle disease associated with aging. It is a disabling disorder still without effective treatment. sIBM causes weakness and atrophy of the distal and proximal muscles. Involvement of quadriceps and deep finger flexors are clues to early diagnosis. Dysphagia in the course of the disease is common. Muscle biopsy shows chronic myopathic features, lymphocytic infiltration invading non-necrotic fibbers, rimmed vacuoles and accumulation of amyloid-related proteins. It remains uncertain whether sIBM is primarily an immune-mediated inflammatory myopathy or a degenerative myopathy with an associated inflammatory component. This review describes the epidemiology and clinical features of the disease as well as the current genetic and pathogenic concepts and therapeutic approaches. Despite recent clues, in many respects sIBM remains an unsolved mystery.